Evaluasi dan Pengendalian Mutu dalam Meningkatkan Daya Saing Lembaga Pendidikan Islam di Indonesia - Muhammad Arif Syihabuddin (Academia Publication, 2022)
Islamic educational institutions in Indonesia face increasingly complex challenges in achieving superior competitiveness. Evaluation and quality control of education is the key to improving the quality and relevance of Islamic educational institutions in the face of global competition. This research uses literature research methods to compile and analyze various references, scientific journals, and official documents related to evaluation and quality control in Islamic educational institutions in Indonesia. The results of the analysis show that first, the evaluation of the quality of Islamic education in Indonesia must include various aspects, such as curriculum, teaching methods, teaching staff, facilities and infrastructure, and the use of technology in learning. Second, active participation from all stakeholders, including lecturers, students, parents, and alumni, is essential in the evaluation process to gain a comprehensive understanding of the advantages and disadvantages of Islamic educational institutions in Indonesia. Third, quality control of Islamic education in Indonesia needs to be supported by an effective and integrated quality management system. A holistic, data-driven approach is the cornerstone of better strategic decision-making. The implementation of nationally and internationally recognized Islamic education quality standards can help increase the credibility of educational institutions and provide trust to the community.